Bare plasmonic metal nanoparticles: synthesis, characterisation and in vitro toxicity assessment on a liver carcinoma cell line. Issue 9 (2nd November 2020) - Das, Nabojit; Kumar, Akash; Kumar Roy, Somendu; Kumar Satija, Neeraj; Raja Gopal, Rayavarapu
Abstract : Metal nanoparticles have generated great interest due to their excellent optical and chemical properties. The widely used chemical method for synthesising nanoparticles involves capping agents for colloidal stability. However, there are scarce reports on the application of metal nanoparticles synthesised without using capping agents. Hence, there is a need to develop pristine nanoparticles devoid of capping that can be used for translational research. Here, the authors developed a facile and rapid method for synthesising bare metal nanoparticles (platinum/silver/gold) that are chemically reactive and stable for a month upon storage. They synthesised bare metal nanoparticles of sub‐15 nm and characterised using standard techniques (UV–VIS‐NIR/DLS/zeta//TEM/XRD). They assessed the safety of the synthesised nanoparticles on the liver carcinoma cell line (HepG2). Bare gold and platinum nanoparticles were non‐toxic in comparison to bare silver nanoparticles. Bare metal nanoparticles were also checked for metal detection wherein antimony, mercury and chromium were detected using bare gold and silver nanoparticles. The spectroscopic shifts of the nanoparticles when bound to metals resulted in blue and red shifting of the plasmon band, indicating the sensing of metals. These results show that bare metal nanoparticles have the potential to emerge as a promising candidate for biomedical and sensing applications.